Welfare and bond pricing implications of fiscal stabilization policies - Kai Christoffel; Ivan Jaccard; Juha Kilponen (Bank of Finland, 2013)
How do cyclical fiscal stabilisation policies affect welfare and government bond risk premia? Using a new Keynesian model we find that the effects of fiscal policy rules on the bond premium and welfare crucially depend on the source of business cycle fluctuations. The overall effect is estimated using Bayesian methods and the mechanism is deconstructed by examining the propagation mechanism of the different shocks. We find that the impact of fiscal policy cyclicality on welfare and risk premia is highly non-linear and that these effects are of a policy relevant magnitude. Finally, we find that the welfare cost of highly procyclical fiscal policies are very large, but also excessive fiscal stabilization can generate non- negligible welfare losses.
URN:NBN:fi:bof-20140807667
Keywords: E5; E6; G1; 330; New Keynesian models; fiscal policy; bond risk premium; monetary policy